The Authenticity of Myriad Things in the Zhuangzi - Hsu, Chiayu (Religions, 2019)
A large quantity of past research in philosophical Daoism has been dedicated to the authenticity of "dao"; this essay shifts the focus to the authenticity of the "myriad things 萬物 (wanwu)" in the Zhuangzi. The concept of "myriad things", which later gains paradigmatic importance in Chinese philosophy, was first introduced in the Laozi and developed in the Zhuangzi. Under the collective heading of "myriad", "myriad things" encompasses all of the variegated existing entities in the empirical world, while also taking into account the individual particularities of each entity without calling forth any singular or set of qualities, or "essence", that is shared by all individuals. As a concept that safeguards individual particularities, the use of "myriad things" in the Zhuangzi serves to counterargue against the essentialist tendency to treat "humans 人 (ren)" as a collective of moral agents with a singular and identifiable moral essence. By the same token, Daoist thinkers re-interpret the meaning of "heaven 天 (tian)" with "the collective name of the myriad things 萬物之總名", thus transferring the transcendent meaning belonging to the former as a transcendent moral authority to the myriad variegated principles that are inherent to each existing and transforming individual. The Daoist theoretical frame breaks away from that of "heaven-human" and connects the re-interpreted "heaven" with concepts of "self-so/self-affirm 自然 (ziran)", ";essentials 情 (qing)", "nature 性 (xing)", and "potency 德 (de)". In this respect, "authenticity 真 (zhen)", as it is warranted by "non-action 無為 (wuwei)", is proposed as an ultimate state of attainment that is identified with the self-realization of each individual being as herself, over and above the so-called moral goodness and its opposite. Furthermore, the self-realization of the authenticity of the myriad things is seemingly paradoxical in the sense that, from the perspective of the "transformation of the myriad things things 萬物之化, the separation between object and subject both exists and is non-existent. The proposition of "myriad things" opposes the essentialization of human beings, whereas the doctrine of the transformation of the myriad things opposes the belief in fixed essentials in individual entities. The road to realizing "authenticity" as herself is thus a never-ending process for each individual member of the myriad things.